Comparison of LFP battery performance between Screw welding and Laser beam welding - Peanjad, Pannawat; Khomfoi, Surin; Phophongviwat, Teeraphon (My University, 2022)
Studying the comparison of the performance of battery packing between screw welding technique and laser beam welding technique, both battery packing techniques have different advantages and disadvantages to different manufacture and assembling. The research is testing the performance of using battery packing in both techniques by choosing the Lithium iron phosphate(LFP) battery manufactured and distributed in the present market. This research will compare the life cycle testing, which tests the battery life performance, testing DC internal resistance of the battery, and comparing the battery's temperature increase while the battery discharged. To collect the performance testing data and choose the most suitable for application use with suitable battery packing technique.
Keywords: Laser beam welding; LFP battery efficiency; Screw welding